Characteristics of Red Algae Bioplastics/Latex Blends under Tension - M. Nizar Machmud; Reza Fahmi; Rohana Abdullah; Coco Kokarkin (Chemical Engineering Diponegoro University, 2013)
Cassava, corn, sago and the other food crops have been commonly used as raw materials to produce green plastics. However, plastics produced from such crops cannot be tailored to fit a particular requirement due to their poor water resistance and mechanical properties. Nowadays, researchers are hence looking to get alternative raw materials from the other sustainable resources to produce plastics. Their recent published studies have reported that marine red algae, that has been already widely used as a raw material for producing biofuels, is one of the potential algae crops that can be turned into plastics. In this work, Eucheuma Cottonii, that is one of the red alga crops, was used as raw material to produce plastics by using a filtration technique. Selected latex of Artocarpus altilis and Calostropis gigantea was separately then blended with bioplastics derived from the red algae, to replace use of glycerol as plasticizer. Role of the glycerol and the selected latex on physical and mechanical properties of the red algae bioplastics obtained under a tensile test performed at room temperature are discussed. Tensile strength of some starch-based plastics collected from some recent references is also presented in this paperDoi: 10.12777/ijse.5.2.81-88 [How to cite this article: Machmud, M.N., Fahmi, R., Abdullah, R., and Kokarkin, C. (2013). Characteristics of Red Algae Bioplastics/Latex Blends under Tension. International Journal of Science and Engineering, 5(2),81-88. Doi: 10.12777/ijse.5.2.81-88